Subtitling Strategies Used in The Meg Movie Texts - Devi Suci Nirwana; Rahmad - Husein; Zainuddin - - (Universitas Negeri Medan, 2021)
The objective of this study is to explain the reason of utilizing subtitling strategies in The Meg movie texts. The research methodology used in the research is qualitative research design. The data were analyzed by using interactive model of qualitative data management and analysis namely data collection, data condensation, data display and verification and conclusion. The findings of this study revealed that the reasons of translator used subtitling strategies in The Meg Movie Texts consisted of historical circumstances, traditions and the strategy to which is accustomed for both the source and the target viewer. The conclusion that the strategy to which is accustomed for both the source and the target viewer as the focused on translator reason used subtitling strategies in The Meg movie texts.Keywords: Movie, Subtitles, Subtitling Strategies, Translation, Texts